Cryogenic thermal insulating and mechanical properties of rigid polyurethane foams blown with hydrofluoroolefin: Effect of perfluoroalkane. (May 2022) - Kim, Tae Seok; Lee, Yeongbeom; Hwang, Chul Hyun; Song, Kwang Ho; Kim, Woo Nyon
The effect of perfluoroalkane (PFA) on the morphology, thermal conductivity, mechanical properties and thermal stability of rigid polyurethane (PU) foams was investigated under ambient and cryogenic conditions. The PU foams were blown with hydrofluorolefin. Morphological results showed that the minimum cell size (153 μm) was observed when the PFA content was 1.0 part per hundred polyols by weight (php). This was due to the lower surface tension of the mixed polyol solution when the PFA content was 1.0 php. The thermal conductivity of PU foams measured under ambient (0.0215 W/mK) and cryogenic (0.0179 W/mK at −100°C) conditions reached a minimum when the PFA content was 1.0 php. The low value of thermal conductivity was a result of the small cell size of the foams. The above results suggest that PFA acted as a nucleating agent to enhanced the thermal insulation properties of PU foams. The compressive and shear strengths of the PU foams did not appreciably change with PFA content at either −170°C or 20°C. However, it shows that the mechanical strengths at −170°C and 20°C for the PU foams meet the specification. Coefficient of thermal expansion, and thermal shock tests of the PU foams showed enough thermal stability for the LNG carrier's operation temperature. Therefore, it is suggested that the PU foams blown by HFO with the PFA addition can be used as a thermal insulation material for a conventional LNG carrier.